The Influence of Tax Management and Financial Ratios on Tax Planning Efficiency of Listed Companies in the Agricultural and Food Industry on The Stock Exchange of Thailand - Suksamai, Phasawat; Mokkhavesa , Benjaporn (ARU Research Journal Humanities and Social Sciences, 2026)
The objective was to examine the influence of tax management and financial ratios on the tax planning efficiency of listed companies in the agricultural and food industry on the Stock Exchange of Thailand. Secondary data were collected from continuous financial statement reports and the SETSMART online database provided by the Stock Exchange of Thailand. The sample consists of 22 listed companies in the agricultural and food industry, with data collected from 2020 to 2024, totaling 110 data sets. Statistical methods used in this research include descriptive statistics, correlation coefficient analysis, and hypothesis testing through multiple regression analysis. The research findings reveal that the financial ratios, specifically the return on assets ratio, had a significant positive influence, and the return on equity ratio had a significant negative influence on the efficiency of tax planning in terms of the effective tax rate, respectively, and both are statistically significant at the 0.01 level. Whereas tax management, namely the book–tax difference, had a significant negative influence on the efficiency of tax planning in terms of both the effective tax rate and the corporate income tax to net cash flow from operating activities ratio, which are statistically significant at the 0.01 and 0.05 levels (respectively). However, deferred tax and the liquidity ratio did not significantly influence the efficiency of tax planning in terms of the effective tax rate. Moreover, deferred tax, the liquidity ratio, the return on assets ratio, and the return on equity ratio did not significantly influence the efficiency of tax planning in terms of the corporate income tax to net cash flow from operating activities ratio.